Aplikasi Chatbot Berbasis Teks Menggunakan Algoritma Naive Bayes Classifier FAQ GrabAds - Rena Cahya Hutama; Fauziah Fauziah; Ratih Titi Komalasari (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
Almost all aspects of human life has been touched by the development of information and communication technology. Especially in the current pandemic where face-to-face interactions are very limited, so sometimes information is not conveyed clearly and precisely. For example, in the case of work when there are new employees who have difficulty getting information or just asking colleagues because they cannot convey information clearly. The lack of access and the amount of access needed to obtain certain information makes it difficult for new employees to work even though the questions asked are the same questions asked by one employee or another. Chatbot is the result of technological innovation that aims to facilitate the process of exchanging information by using interactive programs. With this text-based Chatbot application, you can minimize the time needed to answer questions because it is automated. The Naive Bayes Classifier algorithm was used in making Chatbot in this study by previously creating a collection of frequently arising questions (FAQ) containing 10 questions and their answers which will be used as a dataset. By using a split ratio of 0.8 and a total of 60 questions, the resulting accuracy value is 93.33% and the error value is 6.66%.